Driving Shareholder Value through Technopreneurship Innovation - Sunaryo, Deni; Lestari, Etty Puji; Puryandani, Siti; Hersugondo, Hersugondo (Pandawan, 2025)
The Food and Beverage (F&B) industry in Southeast Asia faces challenges such as raw material price volatility, high debt burden, and changes in consumer preferences, so companies need to manage their financial performance well through financial ratio analysis and product innovation to remain competitive amidst the instability of the ASEAN market and policies. This study analyzes the effect of Return on Assets/ROA, Cash Ratio/CR, Debt to Asset Ratio/DAR, Asset Turnover/ATO, and Price Earnings Ratio/PER on managerial ownership and their impact on stock returns. We assess how product development costs and financial distress moderate the relationship. The objects of the study were F&B sector companies in Southeast Asia listed on the stock exchange, data period 2012 to 2023. The method used was panel data regression. The results showed that ROA and CR positively and significantly affected managerial ownership. Conversely, DAR and PER did not show a significant effect. Moderation of product development costs weakened the impact of ROA on managerial ownership, while financial distress weakened the relationship between DAR and managerial ownership. This study suggests the importance of efficient management of assets, cash, and liabilities and the need for strategic product innovation to maintain and increase managerial ownership. Combining various financial ratios with managerial ownership and their effects on stock returns offers a more comprehensive perspective than previous studies.